Effect of initialC/Nratio on composting of two-phase olive mill pomace, dairy manure, and straw - Ekinci, Kamil; Tosun, Ismail; Kumbul, Barbaros Salih; Sevik, Fevzi; Suluk, Kemal; Bitrak, Necati Berk (Wiley, 2021)
Composting plants should be operated at a high degradation rate in order to lower their capital and operational costs. Initial C/N ratio is one of the most influential factors on the composting process. This study aimed to determine the impacts of initial C/N ratio on operational composting parameters of two-phase olive mill pomace with separated dairy manure. Five initial C/N ratios ranging from 29.43 to 43.33 were examined using fifteen 100 L cylindrical reactors. The highest decomposition rate was estimated at 0.02 day(-1)with the C/N ratio of 34.49. The maximum relative heat generation was obtained with the C/N ratio of 36.07. The C/N ratio of approximately equal to 33 reduced the composting cost of process-based total airflow supplied per dry matter and organic matter loss. The maximum throughput capacity was obtained when the compost blend had the C/N ratio of approximately equal to 37.24. It was concluded that operating the composting of two-phase olive mill waste, separated dairy manure, and straw with the boundary of the initial C/N ratios between 33 and 37 was recommended.
Ekinci, Kamil/0000-0002-7083-5199
Keywords: first-order rate kinetics; relative heat generation; throughput capacity; two-phase olive mill pomace